Performance indicators-based energy sustainability in urban water distribution networks: A state-of-art review and conceptual framework. (September 2021) - Zaman, Dina; Tiwari, Manoj Kumar; Gupta, Ashok Kumar; Sen, Dhrubjyoti
Graphical abstract: Highlights: Low energy consumption in WDNs do not always implicate energy efficiency. Significant energy performance indices prioritized from extensive literature review. Energy efficiency evaluation should not be conducted with system-specific indices. Novel index-based framework for system/operational energy benchmarking is developed. Energy sustainability score (ESS) is proposed for energy benchmarking of WDNs. Abstract: Water distribution networks (WDNs) constitute one of the vital infrastructures of modern cities which consume a significant energy volume. Undermining energy management's importance may lead to system inadequacy even in hydraulically efficient networks and jeopardize its overall sustainability. Several standalone energy-related studies on WDN are available in this context, although a comprehensive review and detailed analysis interlinking the key energy aspects has rarely been conducted. The present study attempts to highlight different energy aspects and their evaluation vis-à-vis development of detailed review-based energy analysis for WDNs by categorizing it into three major themes: energy consumption, energy efficiency, and energy improvement analysis. Existing energy performance indicators/indices (EPIs) are collectively analyzed to ascertain their applicability in energy assessment. Subsequently, a novel framework comprising an abridged list of representative EPIs is derived from these indices for energy assessment of WDNs, and a novel composite index, Energy Sustainability Score (ESS) is introduced to facilitate operational energy benchmarking. The proposed framework is primarily verified through logical deduction and its applicability is demonstrated on a real network. This review-based analysis and the developed framework catalyzes the object-oriented energy management in WDNs, ensuring sustainable and cost-effective operation, guiding policy implementation, and future research in this field.